Revitalizing Bangun Mulya: Harnessing Local Potentials for Sustainable Resilience - Muhammad Ramadhani Kesuma; Lexi Okniel Editya; Annisa Putri; Dimaz Ramadani; Ester Ebuliance Sitompul; Misra; Dita Nurul Hikma; Fitri Hasanah; Hilma Tsania Nur Rahmah; Haslan; Grace Oktavia Jawan (Aksi Kita: Jurnal Pengabdian kepada Masyarakat, 2025)
Bangun Mulya Village, located in Penajam Paser Utara Regency, faces challenges in household waste management, health literacy, digital competitiveness, bullying in schools, and inadequate infrastructure, hindering its environmental, social, and economic resilience. A community service program, conducted from July 14 to August 20, 2025, aimed to revitalize the village by leveraging local potentials to foster sustainable development. Employing a community-based empowerment approach, the initiative utilized mixed-method surveys for needs assessment, implemented individual and group programs, and evaluated outcomes through quantitative and qualitative measures. Interventions included eco-enzyme production training, traditional herbal remedy education, MSME digitalization support, anti-bullying education, natural pesticide training, solar-powered streetlight installation, productive tree planting, establishment of family medicinal plant gardens, and creation of village potential infographics. Results demonstrated significant impacts: 85% of farmers adopted natural pesticides, 90% of participants independently produced herbal remedies, 80% of MSME operators enhanced digital marketing skills, 90% of students showed improved tolerance, 100% participation in tree planting, 70% household adoption of medicinal gardens, and enhanced nighttime safety through functional streetlights. Collaborative community engagement ensured initiative ownership, positioning Bangun Mulya as a more resilient and competitive village, reflecting the role of higher education in sustainable rural development.